Magnetic Resonance Images for the Prediction of Chronological Age Using Maxillary Third Molar Teeth: An Observational Study - Smriti K; Kodali MVRM; Kumar M; Saraf A; Madi M; Pentapati KC; K P; Chhaparwal Y; Kodali US; Gadicherla S (Dove Medical Press, 2024)
Komal Smriti,1,* Murali Venkata Rama Mohan Kodali,2 Mathangi Kumar,1,* Anoushka Saraf,1 Medhini Madi,1 Kalyana Chakravarthy Pentapati,3 Prakashini K,4 Yogesh Chhaparwal,1 Unati Sai Kodali,5 Srikanth Gadicherla6 1Department of Oral Medicine & Radiology, Manipal College of Dental Sciences, Manipal, Manipal Academy of Higher Education, Manipal, Karnataka, 576104, India; 2Department of Oral and Maxillofacial surgery, College of Dentistry, King Faisal University, Al Hofuf, Eastern Province-Al Ahsa, 31982, Kingdom of Saudi Arabia; 3Department of Public Health Dentistry, Manipal College of Dental Sciences, Manipal, Manipal Academy of Higher Education, Manipal, Karnataka, 576104 India; 4Department of Radio Diagnosis, Kasturba Medical College & Hospital, Manipal, Manipal Academy of Higher Education, Manipal, Karnataka, 576104, India; 5Dr Pinnamaneni Siddhartha Institute of Medical Sciences & Research Foundation, Dr. NTR University of Health Sciences, Vijayawada, India; 6Department of Oral & Maxillofacial Surgery, Manipal College of Dental Sciences, Manipal, Manipal Academy of Higher Education, Manipal, 576104, Karnataka, India*These authors contributed equally to this workCorrespondence: Medhini Madi; Yogesh Chhaparwal, Department of Oral Medicine and Radiology, Manipal College of Dental Sciences, Manipal, Manipal Academy of Higher Education, Manipal, Karnataka, 576104, India, Email medhini.madi@manipal.edu; yogesh.chhaparwal@manipal.eduIntroduction: Dental age estimation using third molars is a reliable method for estimating the age of individuals. Recently, magnetic resonance imaging (MRI) of the head and neck has been found to be applicable for age estimation of third molar teeth. In the present study, we aimed to apply the Modified Demirjian method of age estimation to magnetic resonance (MR) image sections for dental age estimation by determining the mineralization patterns of the maxillary third molars.Methods: MRI scans of the patients were performed using SIGNA™ 3.0Tesla MRI GE Healthcare (Chicago, USA) with a moving, multifunctional coil. Two expert radiologists with more than three years of experience independently analyzed the image sections using the open-source Digital Imaging and Communications in Medicine (DICOM) viewer software. The age and sex of the patients whose images were included in the study were recorded using a specially designed proforma. The stage of development of the maxillary third molars was determined using the modified Demirjian method. Inter observer agreement was calculated using the intra class correlation coefficient. Simple linear regression analysis was used to predict the actual age at the third molar development stage.Results: There was excellent agreement between observers (ICC =0.99 (95% CI = 0.98- 0.99)). There was also a significant association between the maxillary third molar tooth development stage and chronological age of the individual (P=0.001; B=1.54; 95% CI = 0.71- 2.37).Discussion: The findings from the present study establish that the Modified Demirjian method can also be reliably applied for dental age assessment in MR sections.Keywords: third molars, forensic science, age estimation by teeth, odontogenesis